Heritage Transmission: Issues of Legal Regulation - I. A. Koryuchina (Сибирское юридическое обозрение, 2022)
The Author considers the hereditary transmission as a special legal phenomenon, analyzes problematic issues of the current legislation and possible ways to resolve them based on the established judicial practice. This topic seemed to the Author quite interesting, despite its obvious lack of demand in the judicial and notarial practice of the last five years. This scientific work is the result of theoretical and practical analysis, both of the entire institute of hereditary transmission, and of such categories (transmission, transmitter, procedural mechanisms) used in cases of inheritance of certain types of property. Important legal aspects of transmission inheritance of property are investigated both in marriage – family and blood – related relations, and in directly related to them, corporate and entrepreneurial. The Author's analysis of inheritance norms is accompanied by a comparison of them with similar norms of foreign legislation. On the example of more than twenty of the most significant court decisions of the Russian judicial authorities, the peculiarities of the system for implementing the institute of hereditary transmission in the Russian Federation and similar institutions in foreign legislation are revealed. Also, on the basis of an integrated approach, the institute of hereditary transmission is investigated in its relationship with various institutions of Russian law and economic analysis of inheritance processes. We believe that business inheritance and inheritance of other types of property, in particular, digital and non-documentary assets, at this stage of the development of Russian legislation is of urgent practical importance, since, transforming and complicating, it is often these relations that significantly affect the subjects of the relations that have arisen and their goals in terms of the implementation of rights and obligations in many areas of public life. We are convinced that the active, continuous development of corporate, family, bankruptcy and intellectual property relations on the one hand and the improvement of Russian legislation on the other will give positive dynamics to the institution of hereditary transmission, simplify the possibilities of its implementation and proof, preserve its significance and essence as one of the most important institutions of Russian hereditary law.